Evolution toward Fit - Siggelkow, Nicolaj (Administrative Science Quarterly, 2002)
This paper uses a longitudinal case study of the mutual fund provider, The Vanguard Group, to understand the developmental processes that lead to organizational configurations and fit. A new method for determining an organization's core elements is developed, and four processes are identified that describe the creation and subsequent elaboration of these core elements: thickening (reinforcement of an existing core element by new elaborating elements), patching (creation of a new core element and its reinforcement by new elaborating elements), coasting (no further elaboration of a new core element in a given period), and trimming (deletion of a core element and its elaborating elements). The four processes are used to describe organizations' development paths toward configurations and their transitions between configurations, including two new ideal types, termed thin-to-thick and patch-by-patch, as well as two known paths between configurations, the punctuated equilibrium path and reorientation through linear progression.